Maternal Outcomes of Pregnancy in Women with Previous One C-Section in Qazi Hussain Ahmad Medical Complex, Nowshehra - Shahzadi Neelam, Sumayya, Adeeba Akhter Khalil, Tayyaba Nawaz, Abgina Bakhtawar, Sami Ur Rahman, M. Mohsin Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This prospective study was conducted to find the maternal outcomes of pregnancy in women with a previous one C-Section in terms of mode of delivery and maternal complication Material & Methods: This prospective cross sectional study was carried out in QHAMC Nowshera from July 2018 to June 2019. A convenient sample of 180 women, all booked and unbooked, with gestational age 37 weeks or more, singleton fetus and cephalic presentation that came to Gynae OPD with history of previous one C/section were included . Informed consent was taken after explaining risks and benefits of planned repeat c/section and VBAC .While those having IUD, placenta previa, breech presentation or gestational age less than 37 weeks were excluded. Data was obtained on pre- designed structured proforma .SPSS 17 software was used for statistical purposes. Results: Results showed that of the total participants 71.1 % had undergone C-section again, and 28.8 % delivered as VBAC. 34.3% of the total C-sections were emergency lower segment C-sections and 65.6% were planned repeat C-sections. Conclusions: It is concluded from our study that VBAC is a safe option for patient with previous one scar with minimal morbidity and no mortality but required good antenatal assessment one to one care and vagilant monitoring with quick resumption to emergency csection when required